2019
DOI: 10.1111/jcmm.14803
|View full text |Cite
|
Sign up to set email alerts
|

Fuziline alleviates isoproterenol‐induced myocardial injury by inhibiting ROS‐triggered endoplasmic reticulum stress via PERK/eIF2α/ATF4/Chop pathway

Abstract: Fuziline, an aminoalcohol-diterpenoid alkaloid derived from Aconiti lateralis radix preparata, has been reported to have a cardioprotective activity in vitro. However, the potential mechanism of fuziline on myocardial protection remains unknown. In this study, we aimed to explore the efficacy and mechanism of fuziline on isoproterenol (ISO)-induced myocardial injury in vitro and in vivo. As a result, fuziline effectively increased cell viability and alleviated ISO-induced apoptosis. Meanwhile, fuziline signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…12 Wsczukidine (7) and miyaconitine (10) have been identified as chemical markers for this species (Figure 8D). The marker for A. transsectum detected in the study, 14-acetyltalatisamine (17), was also isolated and reported from this species by other groups previously. 5,20−22 These 10 selected markers were shown to be present in "high content" in the species as all their Y-axis values exceeded 1000.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…12 Wsczukidine (7) and miyaconitine (10) have been identified as chemical markers for this species (Figure 8D). The marker for A. transsectum detected in the study, 14-acetyltalatisamine (17), was also isolated and reported from this species by other groups previously. 5,20−22 These 10 selected markers were shown to be present in "high content" in the species as all their Y-axis values exceeded 1000.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…For example, fuziline has reported cardioprotective activity in vitro and in vivo. 17 Because these four markers are rarely present in other tissues of A. carmichaelii or related species, its lateral root (i.e., fuzi) has been used in traditional medicine, and the other parts (e.g., flowers, stem, or stems) are seldomly used. 1 Similarly, markers present in cluster A (Figure 4, bottom) were identified as carmichaenines D (21), C ( 22), (−)-(A-b)-14α-benzoyloxy-N-ethyl-1α, 8β, 15α-trihydroxy-16β, 18-dimethoxyaconitane (24), and 14-benzoylneoline (41), which are markers for flowers of A. carmichaelii.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ATF4 increases the production of ROS, which can also be proapoptotic. The importance of ATF4 was demonstrated by blocking its transcription, which promoted apoptosis [43,44]. In contrast, translation of CHOP stimulates the transcription of protein phosphatase 1 regulatory subunit 15 (PPP1R15A/GADD34), TNF-related apoptosis-inducing ligand (TRAIL2), tribbles homolog 3 (TRB3), and, as a consequence, endoplasmic reticulum disulphide oxidase 1α (Ero1α).…”
Section: Participation Of Phospholipid Metabolism Products In Apoptosismentioning
confidence: 99%
“…ATF4 overexpression can trigger a cascade of ROS and induce apoptosis ( Wortel et al, 2017 ; Zong et al, 2017 ). On the contrary, the disorder of ATF4 alleviates the ROS production and apoptotic process in various tissues and cell types ( Fan et al, 2020 ). As an upstream of ATF4, the phosphorylation of eukaryotic initiation factor-2α (eIF2α) preferentially facilitates the ATF4 activation, which transduces signals to the cytoplasm and nucleus to cause the imbalance of cellular homeostasis ( Harding et al, 2003 ; Liu and Zhang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%